EFEK LATIHAN FISIK TERATUR DAN TERUKUR PADA TIKUS SPRAGUE DAWLEY JANTAN DIABETES INDUKSI STREPTOZOTOCIN DALAM MENCEGAH KOMPLIKASI GINJAL - , Diyah Candra Anita K; , dr. Sri Lestari Sulistyorini, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background. The main cause of complications in diabetes mellitus is a condition of oxidative stress due to increased reactive oxygen species (ROS). The increase in ROS can be triggered by the increase in advanced glycation end-products (AGE), which binds to its receptor (RAGE). The result of increased ROS will lead to lipid peroxidation in cell membranes and induce particular increase in malondialdehyde (MDA). The objective of this study was to evaluate the benefits of physical exercise in preventing complications of the kidney caused by hyperglycemia. Methods. This study was a pure experimental research with post-test only group design. Subjects were 10 male Sprague Dawley rats induced with 35 mg/kg dose of streptozotocin (STZ). The subjects were divided into two groups, i.e. the STZ group and STZ group with physical exercise. Physical exercise was given in 9 weeks using a treadmill, in 5 days of exercise/week, moderate intensity, 0 degree of tilt, gradually increased speed and duration. Results. Regular and measurable physical exercise can decrease the blood glucose level (0,048) and reduce the RAGE expression in glomerulus (0,003) but increase MDA level in kidney (0,767). Conclusion. Regular and measurable physical exercise can decrease the blood glucose level and reduce the RAGE expression in glomerolus.